GLOBAL MARKETING AND ADVERTISING UNDERSTANDING CULTURAL PARADOXES - Widya Paramita (Journal of Indonesian Economy and Business (JIEB), 2014)
A book review on Global Marketing and Advertising to Understand Cultural Paradoxes.